Biodiversity of anuran endoparasites from a transitional area between the Atlantic Forest and Cerrado biomes in Brazil: new records and remarks - Aguiar, Aline; Morais, Drausio Honorio; Silva, Lidiane A. Firmino; Anjos, Luciano Alves Dos; Foster, Ottilie Carolina; Da Silva, Reinaldo José (Zootaxa, 2021)
The richness of metazoan endoparasites associated with 25 anuran species from a transitional area between Cerrado and Atlantic Rain Forest from Brazil is here presented. We present and discuss the type-host and localities, the current taxonomic status, remarks on morphological features, biological cycle, and new records of these parasites. Nine hundred and seventy-eight anurans of four families (Bufonidae, Hylidae, Microhylidae, and Leptodactylidae) were collected during four expeditions in a private forested area from Northwest of São Paulo state. The richness of metazoan parasites was composed of nematodes (21), acanthocephalans (2), digeneans (18), monogeneans (1), cestodes (1), and oligochaetes (1), resulting in 44 taxa that are presented with their respective prevalence and the range of abundance in host populations. Among these parasites, nine were found in immature stages which usually complete their life cycle in fishes, snakes, birds or mammals, attesting the trophic relation of amphibians and their parasites within the regional vertebrate community. We reported 23 anuran species as new hosts resulting in 79 new associations between anurans and parasites. Gorgoderina diaster and Bursotrema tetracotyloides are reported for the first time in Brazil, and our finding of Clinostomum cf. complanatum represents the first in South American anurans.